1999
DOI: 10.1890/1051-0761(1999)009[0824:bpaaof]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Bias, Precision, and Accuracy of Four Measures of Species Richness

Abstract: Species richness is a widely used surrogate for the more complex concept of biological diversity. Because species richness is often central to ecological study and the establishment of conservation priorities, the biases and merits of richness measurements demand evaluation. The jackknife and bootstrap estimators can be used to compensate for the underestimation associated with simple richness estimation (or the sum of species counted in a sample). Using data from five forest communities, we analyzed the simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
118
1
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(127 citation statements)
references
References 21 publications
3
118
1
5
Order By: Relevance
“…Herein, we define accuracy as the difference between an estimate and the true value of the population, here estimated from the largest sample available, and precision as the variance of the estimates (Hellmann and Fowler, 1999). In consequence, accuracy is measured with a bias estimator, and precision with standard errors and related measures.…”
Section: Adult Genetic Diversity Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, we define accuracy as the difference between an estimate and the true value of the population, here estimated from the largest sample available, and precision as the variance of the estimates (Hellmann and Fowler, 1999). In consequence, accuracy is measured with a bias estimator, and precision with standard errors and related measures.…”
Section: Adult Genetic Diversity Evaluationmentioning
confidence: 99%
“…The bias of the estimators was evaluated by joint analysis of the coefficient of variation and the mean square error following Kirst et al (2005). In this framework, the bias is the difference between the expected value of the estimator (the mean of the estimates of all possible samples that can be taken from the population) and the true population value (Hellmann and Fowler, 1999). Hence, we used the formula:…”
Section: P2mentioning
confidence: 99%
“…4-26.7, 35.6-41.3 and 63.6-66.7% of total samples. In a similar study, Hellmann and Fowler (1999) found that for Jackknife 1, Jackknife 2 and Boot, the sub-sample size needed to estimate richness in the total sample were, respectively, 22. 6-29.1, 36.8-43.9 and 63.1-69.0% of total samples.…”
Section: Discussionmentioning
confidence: 87%
“…These approaches include measures of bias and accuracy of the estimated richness in relation to the true richness using an a priori chosen sub-sample size. However, the estimated richness is strongly dependent on sample size (Colwell and Coddington, 1994;Melo and Froehlich, 2001;Petersen and Meier, 2003) and different sub-samples sizes will produce different bias and accuracy values (Hellmann and Fowler, 1999). In addition, these approaches require data for maximum species numbers for their calculation, so they cannot be used here.…”
Section: Evaluation Of Estimator Performancementioning
confidence: 99%
“…Under these circumstances, few species richness estimators have performed well in Monte Carlo simulations with actual forest inventory data (Magnussen, 2011;Magnussen et al, 2010). Heretofore popular estimators of richness like the Jackknife, the bootstrap, and Chao's coverage-based estimators generally disappoint because they were not designed for sampling with multi-tree quadrants (Hellmann & Fowler, 1999;Hwang & Shen, 2010;Lam & Kleinn, 2008;Palmer, 1991;Schreuder et al, 2000;Schreuder et al, 1999).…”
Section: Introductionmentioning
confidence: 99%